Implementasi Nilai Shidq, Amanah, Istiqamah, dan Rahmah dalam Pembinaan Akhlak Siswa SMK Al-Azami - Alfa Rohmatin; Yuda Nugraha; Moch. Galih Gunawan; M. Ramanda Iski (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the characteristics of SMK Al-Azami students in emulating the morals of the Prophet Muhammad (peace be upon him) as part of character development based on Islamic values within vocational education. The background of this research lies in the urgency of character education that not only emphasizes academic competence and technical skills but also focuses on moral formation and professional ethics. This research employed a qualitative approach using a library research method by analyzing relevant classical and modern Islamic literature, supported by documentation of school activities. The results reveal that the moral values of the Prophet Muhammad have been well internalized in students’ daily behavior, which includes four core dimensions: Shidq (honesty), Amanah (trustworthiness), Istiqamah (discipline), and Rahmah (compassion). The value of Shidq is reflected in students’ honesty during vocational practice and in reporting work results; Amanah is demonstrated through responsibility for tools and group tasks; Istiqamah appears in punctuality, consistency, and work discipline; and Rahmah is shown through respectful, empathetic, and cooperative social interactions. The findings indicate that Islamic character education effectively shapes students with integrity, discipline, and social awareness, serving as a model for moral development in vocational schools. Furthermore, this research highlights the importance of strengthening teacher exemplarity, religious habituation, and curriculum integration of Islamic moral values in vocational learning to ensure sustainable character development.